Simple Shear Mechanism to Revealing Geological Complexity of Geosite Assessment in the Bukit Duabelas National Park Jambi Province, Indonesia - Hari Wiki Utama; Rakhmatul Arafat; Bagus Adhitya; Yulia Morsa Said; Arsyad AR; Gindo Tampubolon; Agus Kurniawan Mastur; Itang Ahmad Mahbub; Yusmansyah Siregar; Ignatia Tri Astuti; M. Fauzi Fauzi (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Bukit Duabelas National Park (BDNP) Jambi Province is a national protected area that has geodiversity. BDNP forms northwest – southeast oriented, morphologically connected to the Barisan Mountains by the Bangko Basin. Digital elevation model observations show that the morphological orientation of these hills is surrounded by valleys and plains occupied by Paleogene-Neogene sedimentary rocks. The presence of Schist Terantam Formation provides interesting information about the exposed basement. This research uses remote sensing, field observations and stratigraphic analysis, as well as assessing geological complexity. The BDNP Territory is geologically influenced by geological structures such as faults and folds as a result of the simple shear deformation mechanism. Schist from the Terantam Formation and Granite and Pegmatite Intrusions are a consequence of simple shear mechanisms and tectonic orogenesis. Geological complexity of geosite assessment based on the criteria of petrological features, landscape, age of formation, fossil appear, tectonic basement, basement group, cultural diversity, other geological information. The proposed geosite is Terantam Inselberg which is composed of the Terantam Formation of Carboniferous and Jurassic-age of Granite and Pegmatite. The uniqueness of this proposed geosite is that the rocks exposed are the oldest basement rocks on the Sumatra Island. The landscape with Inselberg morphology, of course, is unique and is very rarely found in other areas, then the presence of ethnic groups from the Inner Child Tribe who inhabit the area characterizes cultural diversity. Comparing this proposed geosite with geosites of national and international value in the MJUGGp Territory, it can be concluded that the Terantam Inselberg Geosite is in between the two positions.